Enhancing the professional direction of university students: on the experience of the academic curator - Galina Vitalievna Buyanova (Вестник Майкопского государственного технологического университета)
The problem of finding ways to enhance the professional orientation of young people receiving their first higher education is actualized by the target setting of modern higher education for the training of qualified, mobile and competitive specialists, on the one hand, and the poor professional orientation of university, on the other hand. The authors adhere to the point of view that the formation of a professional orientation in the aggregate of its three main components (value, motivational and cognitive-reflective ones) must begin with the latter, because only on the basis of existing adequate knowledge of a profession a young man has the opportunity to compare them with his own needs and capabilities, which, in turn, becomes a material for the development of professional-value orientations and motivation for the development of a particular profession. The purpose of the article is to describe the results of an empirical study of the cognitive-reflective component of the professional orientation of agricultural students according to the results of two years of curator work with a group following the author's program for activating professional orientation. The study of the level of awareness of respondents about their future profession was carried out using the author's questionnaire "I am in the profession." The result of the study was a significant shift in the experimental group from a lower level to a higher one in all indicators of the studied component of the professional orientation, which confirms the positive experience of the academic curator.